Morphological and morphometric characteristics of gastric mucosa in western grey kangaroo (Macropus fuliginosus) (Journal of Advanced Veterinary and Animal Research, 2014)
The present study was aimed to investigate the morphology and histomorphometry of stomach and gastric mucosa in western grey kangaroo (Macropus fuliginosus). The stomach was composed of three indistinctive separate parts namely sacciform forestomach, tubiform forestomach, and hindstomach. The tubiform forestomach was the main tubular section of the organ. The stomach had a compound lining. The non-glandular mucosa occupied the medial blind sac (MBS) of the sacciform forestomach; the layer covered about one-third of the tubiform forestomach (non-glandular region) and the entire length of the gastric sulcus. The glandular part lined the parietal blind sac (PBS) of sacciform forestomach and the cardiac gland region of tubiform forestomach as well as fundic and pyloric gland regions of the hindstomach. The cardiac mucosa had smooth and folded areas; these were filled with mixed glands. In the fundic glands, the parietal cells outnumbered the chief cells. The pyloric glands were of serous-like in characteristics. In conclusion, gross and histological structures of the stomach of western grey kangaroo are adaptive with its food habitat, which allows thorough mixing of highly fibrous grasses. http://dx.doi.org/10.5455/javar.2015.b43